Blunt traumatic diaphragmatic hernia: Pictorial review of CT signs - Kaur, Ravinder; Prabhakar, Anuj; Kochhar, Suman; Dalal, Usha (Indian Journal of Radiology and Imaging, 2015)
Blunt diaphragmatic rupture rarely accounts for immediate mortality and may go clinically silent until complications occur which can be life threatening. Although many imaging techniques have proven useful for the diagnosis of blunt diaphragmatic rupture, multidetector CT (MDCT) is considered to be the reference standard for the diagnosis of diaphragmatic injury. Numerous CT signs indicating blunt diaphragmatic rupture have been described in literature with variable significance. Accurate diagnosis depends upon the analysis of all the signs rather than a single sign; however, the presence of blunt diaphragmatic rupture should be considered in the presence of any of the described signs. We present a pictorial review of various CT signs used to diagnose blunt diaphragmatic injury. Multiplanar reconstruction is very useful; however, predominantly axial sections have been described in this pictorial review as the images shown are from dual-slice CT.
Keywords: Computed tomography; diaphragm; hernia; injury; trauma